Prevalence of Acid alpha-Glucosidase (GAA) Pseudodefiency Allele and It’s Clinical Significance Among Patients with Cardiomyopathy - Han Bing, Chow; H, S, Ling; E. Z., Chan; B. K., Chung; L. K.`, Then; I. X., Pang; H. K., Khor; S. T., Chan; C. T., Tan; K. T.`, Koh; Y. L., Cham; Asri, Said; et al. (Elsevier B.V., 2022)
Background: Pompe disease is an autosomal recessive lysosomal storage disorder caused by deficiency of lysosomal acid alpha-glucosidase (GAA) activity, leading to the progressive accumulation of glycogen in lysosomes of the skeletal and cardiac muscles. An alpha-glucosidase (GAA) pseudodeficiency allele is a change in the GAA gene sequence that results in GAA enzyme activity reduction, but does not cause Pompe disease. In Japan and Taiwan, there is high prevalence of pseudodeficiency allele (c.1725G>A and c.2065G>A) detected from their newborn screening. We observed similar prevalence of pseudodeficiency allele among our patients who had genetic test performed for suspected hereditary cardiomyopathy.